(untitled) (Nepalese Journal of Radiology, 2012)
Interruption of the pulmonary artery is a rare congenital disorder. The clinical symptoms are non-specific and radiological investigations are the key to diagnosis. We present a case of interruption of the left pulmonary artery associated with Tetralogy of Fallot in a young male. The radiological and clinical features of this condition are also reviewed. DOI: http://dx.doi.org/10.3126/njr.v1i1.6322 Nepalese Journal of Radiology Vol.1(1): 37-40